Perencanaan dalam Pengembangan Wisata Sungai Kali Banger di Kelurahan Kali Baros - Alifah Fidela; Nadya Ramadhanty; Akhmad Arifin Hadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Indonesia has a wealth of natural resources, tourism and other potential that can be developed, but rivers are often overlooked. The development of the river as a tourist area is still limited to rafting, canoeing and fishing. Tourism by going along the river using a boat or boat is still not worked seriously. Kali Banger River is one of the cleanest rivers that has not been contaminated with waste so that it is used as a source of irrigation by the people of Kali Baros Village for their rice fields. But unfortunately, the development of river tourism is still constrained in several ways, namely the pile of garbage on the side of the river road and the homeless people living in Tahura. The purpose of the